Pengembangan Sistem Informasi Inventarisasi Aset menggunakan Metode Test Driven Development (Studi Kasus: Universitas Mulia) - Ranu Goldan Yeara Elzatar; Adam Hendra Brata; Agi Putra Kharisma (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2022)
Technology requires an effective and efficient system that is supported by a database to process information data, one of which is the asset inventory information system. Assets are reported by the organization to increase value as well as provide operational benefits to the organization. The more assets owned, the organization needs to have a system to carry out an inventory of these assets, especially related to detailed information. This is very useful for improving performance in an organization such as a university. One of the universities that is still not efficient in inventorying assets is Mulia University. The purpose of this research is to carry out an effective and efficient asset inventory by building information system software to assist the operational performance of Mulia University. In building this research, a Test-Driven Development (TDD) approach is needed so that the design is more systematic and flexible if changes occur. In addition, early detection of defects or errors makes it easier to correct changes early in the development process thereby saving time and money in the long run. Then, the testing technique used is black box and white box. The results obtained from this study are information systems for asset inventory can provide solutions to problems in asset management at Mulia University.